2017
DOI: 10.3389/fimmu.2017.00028
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 and TLR3 Sense Brucella abortus RNA to Induce Proinflammatory Cytokine Production but They Are Dispensable for Host Control of Infection

Abstract: Brucella abortus is a Gram-negative, facultative intracellular bacterium that causes brucellosis, a worldwide zoonotic disease leading to undulant fever in humans and abortion in cattle. The immune response against this bacterium relies on the recognition of microbial pathogen-associated molecular patterns, such as lipoproteins, lipopolysaccharides, and DNA; however, the immunostimulatory potential of B. abortus RNA remains to be elucidated. Here, we show that dendritic cells (DCs) produce significant amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…Staying inside vesicular compartments throughout most of their intracellular life is one of the strategies developed by stealthy pathogens to hide from cytoplasmic innate immune receptors. However, endosomal receptors such as TLR3, TLR7-8 and TLR9, also take part in Brucella recognition ( Gomes et al, 2016 ; Campos et al, 2017 ; Milillo et al, 2017 ) and likely encounter BCVs during bacterial intracellular trafficking. Since vesicular traffic is largely performed by MTs, we investigated whether treatment of infected macrophages with nocodazole, paclitaxel or rTcpB could also affect innate immune responses against Brucella infection.…”
Section: Resultsmentioning
confidence: 99%
“…Staying inside vesicular compartments throughout most of their intracellular life is one of the strategies developed by stealthy pathogens to hide from cytoplasmic innate immune receptors. However, endosomal receptors such as TLR3, TLR7-8 and TLR9, also take part in Brucella recognition ( Gomes et al, 2016 ; Campos et al, 2017 ; Milillo et al, 2017 ) and likely encounter BCVs during bacterial intracellular trafficking. Since vesicular traffic is largely performed by MTs, we investigated whether treatment of infected macrophages with nocodazole, paclitaxel or rTcpB could also affect innate immune responses against Brucella infection.…”
Section: Resultsmentioning
confidence: 99%
“…abortus RNA to induce the production of pro-inflammatory cytokines and type I IFN expression in murine DCs. However, these receptors were not required to control Brucella infection in vivo [ 39 ]. To explain the latter, they hypothesized that TLR13, a PRR involved in sensing a specific sequence from bacterial 23S rRNA [ 40 , 41 ], could play a role in B .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the role of toll-like receptors (TLR) was demonstrated to affect the production of IL-6 and IL-12 simulated by Brucella RNA in vitro. The authors added that brucella ribonucleic acid had significant immunostimulatory function, and the cytokines released by dendritic cells in the response to this stimulation were TLR-dependent [23]. In another study carried out on 173 patients with Saadati et al…”
Section: Discussionmentioning
confidence: 99%